Automatisation of make-up process of advertisements in periodicals - Романовская, Владислава Евгениевна; Бизюк, Андрей Валериевич; Некрасова, Наталья Николаевна (Technology audit and production reserves, 2013)
The main objective of the study was to determine the principles of advertising and to consider the software, which would permit to avoid repetitive actions, when making-up periodicals. The relevance of the study is determined by the insufficient examination of automation devices of advertising making-up, taking into account the factors affecting advertising effectiveness, the need for practical study of perception and effectiveness of advertising messages, the possibility of practical application of the results. This will make it possible to find new ways to ensure maximum publicity of advertising, which in turn will increase sales. The article presents recommendations for an automated making-up of newspaper advertising. It considers specialization of the most popular software for making-up and peculiarities of the application of software, designed for a particular query. We have created a set of recommended components of the automation advertising making-up system, which can be the basis for further improvement of the efficiency of an enterprise functioning.